2012
DOI: 10.1371/journal.pone.0044087
|View full text |Cite
|
Sign up to set email alerts
|

Elevating SOX2 Levels Deleteriously Affects the Growth of Medulloblastoma and Glioblastoma Cells

Abstract: Medulloblastomas and glioblastomas are devastating tumors that respond poorly to treatment. These tumors have been shown to express SOX2 and overexpression of SOX2 has been correlated with poor prognosis. Although knockdown of SOX2 impairs the growth and tumorigenicity of brain tumor cells, it was unclear how elevating SOX2 levels would affect their fate. Interestingly, studies conducted with neural stem cells have shown that small increases or decreases in the level of this transcription factor significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 40 publications
9
61
0
2
Order By: Relevance
“…Sox4, Sox2, and Oct4 were the three genes responsible for the stemness retained in glioma stem cells, which were overexpressed in stem cells, and reduction of which induced stem cell differentiation [11][12][13]. In this study, our results showed that Sox4, Sox2, and Oct4 were overexpressed in the stem-like spheres, which were induced by curcumin.…”
Section: Introductionsupporting
confidence: 52%
“…Sox4, Sox2, and Oct4 were the three genes responsible for the stemness retained in glioma stem cells, which were overexpressed in stem cells, and reduction of which induced stem cell differentiation [11][12][13]. In this study, our results showed that Sox4, Sox2, and Oct4 were overexpressed in the stem-like spheres, which were induced by curcumin.…”
Section: Introductionsupporting
confidence: 52%
“…For example, stable expression of the transcription factor SOX2 in neoplastic cells enriches a subpopulation with enhanced growth, [13][14][15] whereas rapid induction of SOX2 levels via an inducible system leads to dramatic decreases in the growth of some cells. 16,17 Therefore, we engineered BxPC3 and Capan1 cells with a stably integrated, Dox-inducible USP9X shRNA vector. More specifically, we employed a lentiviral vector that constitutively expresses the reverse tet-transactivator, as well as introduces an USP9X shRNA construct with an associated red-fluorescent protein reporter, under the control of a tetresponsive element (Fig.…”
Section: Stable Knockdown Of Usp9x Reduces the Growth Of Pdac Cellsmentioning
confidence: 99%
“…While this study focuses on the role of SoxB1 protein in the regulation of stem and progenitor cells in the healthy brain, it is notable that reduced Sox2 expression levels are a hallmark of gastric cancers and high levels of Sox2 have tumor suppressor functions in brain cancer cells (Cox et al, 2012). In addition, it is tempting to speculate that other Sox transcription factors may employ a similar regulatory mechanism in controlling precursor self-renewal.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses conducted both in the developing and adult CNS demonstrate that SoxB1 protein function is both sufficient and a prerequisite to maintaining cells in a mitotically active precursor state (Sarkar and Hochedlinger, 2013). Despite this fact, overexpression or misexpression of SoxB1 proteins in immortalized cells in vitro has actually been shown to reduce their proliferation rate (Cox et al, 2012;Otsubo et al, 2008), while removal of one of the SoxB1 genes, Sox2, causes quiescent Muller-glia progenitors in the adult mouse retina to become mitotically active (Surzenko et al, 2013). However, the mechanisms by which differences in Sox2 expression levels can alter a cell's cell-cycle kinetics are not understood.…”
Section: Introductionmentioning
confidence: 99%